Оцінки найкращих наближень класів нескінченно диференційовних функцій у рівномірній та інтегральних метриках - Сердюк, А.С.; Степанюк, Т.А. (Український математичний журнал, 2014)
Найдены равномерные относительно параметра p,1≤p≤∞, оценки сверху наилучших приближений тригонометрическими полиномами классов периодических функций Cψβ,p, порождаемых последовательностями ψ(k), убывающими к нулю быстрее любой степенной функции. Полученные оценки точны по порядку и содержат выраженные в явном виде постоянные, зависящие только от функции ψ. Аналогичные оценки установлены для наилучших приближений классов Lψβ,1 в метриках пространств Ls,1≤s≤∞. We establish uniform (with respect to the parameter p, 1 ≤ p ≤ ∞) upper estimations of the best approximations by trigonometric polynomials for the classes C β,p ψ of periodic functions generated by sequences ψ(k) vanishing faster than any power function. The obtained estimations are exact in order and contain constants expressed in the explicit form and depending solely on the function ψ. Similar estimations are obtained for the best approximations of the classes L β,1 ψ in metrics of the spaces L s , 1 ≤ s ≤ ∞.